The Effect of Corporate Governance on Green Banking Disclosure in Indonesian Islamic Banking for the 2019-2021 Period - Fazadilla, Afizha Nurul; Waskito, Iman (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to examine the effect of corporate governance on the disclosure of green banking in Islamic banking in Indonesia for the 2019-2021 period. This study looks at Islamic banking registered with the Otoritas Jasa Keuangan (OJK) as a population, and the sample consists of 9 Islamic banks selected through purposive sampling. During the observation period, this study assessed green bank disclosures through the annual reports of Islamic banks. The content analysis method was used to conduct this evaluation. Multiple linear regression analysis was used to examine the causal relationship between green bank disclosure and corporate management. The results of this study found that there is an influence between the size of the board of commissioners on green banking disclosure in Islamic banking in Indonesia. as well as the sharia supervisory board has an effect on green banking disclosure.